Investigation of Spectrophotometrical and Fluorescent Behavior of 1,3-Diethyl-5-(Quinoline-2-Ylmethylene)-2-Thioxodihydropyrimidine-4,6(1H,5H)-Dione in Various Solvents - Canlica, Mevlude; Beker, H. Kerim; Ozyigit, Ibrahim E.; Akinci, Alper; Kaban, Seniz (SPRINGER, 2009)
Heterocyclic compounds containing atoms of the elements such as nitrogen, sulfur and oxygen as ring members are commonly used in various fields of industry as analytical reagents, ligands, dyestuffs, pharmaceutical substances and bioindicators. In this study 5-(Quinoline-2-ylidene)-1,3-diethyl-2-thiobarbituric acid have been synthesized via Knoevenagel condensation reaction, the product solutions were prepared 10(-3)-10(-5) M in CHCl3, THF, MeOH, DMF and DMSO. UV/VIS spectra recorded and then compared at each other. Absorbance of the solutions were measured at 200-300 nm. The maximum absorbance value increased and a new absorption appeared at 400-500 nm. The samples were excited at 337 nm in order to measure fluorescence. The maximum emission was observed in MeOH at 398 nm. These values increased by timed therefore, the samples were not stable in solution state.
Keywords: Fluorescence; Heterocyclic compound; Knoevenagel condensation; Spectroscopy; CONDENSATION; Biochemistry & Molecular Biology; Chemistry